ISLAM DAN FILOSOFI MASYARAKAT FAKFAK - Mohamadon D.Husen (Wahana Islamika: Jurnal Studi Keislaman, 2018)
Fakfak community is known as religious society, friendly, goodmanners, maintaining tolerance among religious people, appreciatingunity and unity because everything is contained in the philosophy andoutlook of life. Philosophy of society Fakfak is a life view that wasexcavated and formed based on mutual consensus that contains thenoble values of the people of Fakfak itself since time immemorial whichthen used as a bond and then the philosophy or life view is used as aguide and even motivation in running various aspects people's lives.The philosophy contains a substance where all attitudes and worldviewsare based on "family religion" or "custom, religion and government"which are summed up into “satu tungku tiga batu”. Thus when theoccurrence of Islamic transformation in the land of Papua and in Fakfakin particular it does not necessarily replace the existing values of Islamin the life of the people of Fakfak, even some aspects of the philosophy ofsociety Fakfak is in line with the spirit of Islamic teachings as a religionthat brings present "Grace" for nature and its contents including forthe people of Fakfak.